2001
DOI: 10.1007/s004640080093
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of thoracoscopic splanchnicectomy for chronic pancreatitis pain

Abstract: Thoracoscopic SPL offers short-term relief of pain from chronic pancreatitis, but the relief is not durable in most cases. Similarly, there are short-term improvements in degree of disability, mood, and freedom from narcotic use that are not sustained in the long-term. Nevertheless, two-thirds of patients stated that they would have the surgery again.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…These results are coherent with other authors [1][2][3][6][7][8][9]. However, it was noticed that, not equally in all patients, the pain reduction could be achieved.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are coherent with other authors [1][2][3][6][7][8][9]. However, it was noticed that, not equally in all patients, the pain reduction could be achieved.…”
Section: Discussionsupporting
confidence: 93%
“…It is a method not requiring especially long training for both monolateral and simultaneous bilateral procedure [4,5]. Despite promising results at the initial phase after the introduction of this method, the late quality-of-life results and satisfaction from the surgery are not definite [6][7][8]. Howard et al [9] suggested that the recurrence of pain ailments after VSPL can be due to nerve fiber architecture rearrangements and secondary neuropathic pain after upper abdomen surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, surgical trials based on such scant information often lead to uneven degrees of symptom relief. Success rates for pain management following splanchnicectomy vary from 60 to 90% between different surgeons (Pietrabissa et al, 2000;Leksowski, 2001;Maher et al, 2001;Makarewicz et al, 2003). These results are not due to the differing level of skill among surgeons but to the lack of established surgical protocol based on well-defined anatomical information.…”
Section: Introductionmentioning
confidence: 76%
“…One-third to half of these patients have shown good reduction of pain in a short-term follow-up; however, only 10% of them seem to show a benefit at 24 weeks [64]. Many studies [64][65][66] show that the early good results achieved by neuroablative procedure decline with time elapsed as compared with the durable relief obtained from conventional surgical procedures. Over twothirds of patients would ultimately need surgery again [66].…”
Section: Surgery Vs Neuroablative Proceduresmentioning
confidence: 99%
“…Many studies [64][65][66] show that the early good results achieved by neuroablative procedure decline with time elapsed as compared with the durable relief obtained from conventional surgical procedures. Over twothirds of patients would ultimately need surgery again [66]. Patients who are at a high risk for surgery or deny it and who those have failed to respond to surgical management can be offered neuroablative procedure, although larger data are needed to support its routine role.…”
Section: Surgery Vs Neuroablative Proceduresmentioning
confidence: 99%